Survey of socio-economic and contextual factors of households׳ energy consumption - Omar Jridi (Data in Brief, 2015)
We present a set of data relating to the investigation of the Tunisian Company of Electricity and Gas (STEG). The census is done on a sample of 3000 electrified households. The questionnaire is divided into three main sections: household socioeconomic status, contextual characteristics related to their housing and technical characteristics of equipments used. The objective of this survey is to achieve a reliable and detailed knowledge on the behavior of household energy consumption, particularly for energy saving behavior. This objective has recently been the subject of a research article Jridi et al. (2015) [2].